A High-Protein, Low Glycemic Index Diet Suppresses Hunger but Not Weight Regain After Weight Loss: Results From a Large, 3-Years Randomized Trial (PREVIEW) - Zhu, Ruixin; Fogelholm, Mikael; Larsen, Thomas M.; Poppitt, Sally D.; Silvestre, Marta P.; Vestentoft, Pia S.; Jalo, Elli; Navas-Carretero, Santiago; Huttunen-Lenz, Maija; Taylor, Moira A.; Stratton, Gareth; Swindell, Nils; et al. (Frontiers in Nutrition, 2021)
Background: Previous studies have shown an increase in hunger during weight-loss maintenance (WLM) after diet-induced weight loss. Whether a combination of a higher protein, lower glycemic index (GI) diet and physical activity (PA) can counteract this change remains unclear. Aim: To compare the long-term effects of two diets (high protein (HP)-low GI vs moderate protein (MP)-moderate GI) and two PA programs (high intensity (HI) vs moderate intensity (MI)) on subjective appetite sensations during WLM after ≥8% weight loss (WL). Methods: Data derived from the 3-year PREVIEW randomized intervention study. An 8-week WL phase using a low-energy diet was followed by a 148-week randomized WLM phase. For the WLM, participants were assigned to one of the four groups: HP-MI, HP-HI, MP-MI, and MP-HI. Available data from 2,223 participants with overweight or obesity (67.6% women; BMI≥25 kg/m2). Appetite sensations including satiety, hunger, desire to eat, and desire to eat something sweet during the two phases (at 0, 8 weeks and 26, 52, 104, and 156 weeks) were assessed based on the recall of feelings during the previous week using visual analogue scales. Differences in changes in appetite sensations from baseline between the groups were determined using linear mixed models with repeated measures. Results: There was no significant diet×PA interaction. From 52 weeks onwards, decreases in hunger were significantly greater in HP-low GI than MP-moderate GI (Ptime×diet=0.018, Pdiet group=0.021). Although there was no difference in weight regain between the diet groups (Ptime×diet=0.630), hunger and satiety ratings correlated with changes in body weight at most timepoints. There were no significant differences in appetite sensations between the two PA groups. Decreases in hunger ratings were greater at 52 and 104 weeks in HP-HI vs MP-HI, and greater at 104 and 156 weeks in HP-HI vs MP-MI. Conclusions: This is the first long-term, large-scale randomized intervention to report that a HP-low GI diet was superior in preventing an increase in hunger, but not weight regain, during 3-year WLM compared with a MP-moderate GI diet. Similarly, HP-HI outperformed MP-HI in suppressing hunger. The role of exercise intensity requires further investigation. Clinical Trial Registry: ClinicalTrials.gov registry ID NCT01777893.